"More Splendid than the Sun": Christ's Flesh among the Reasons for the Incarnation. (22nd July 2019) - Case, Brendan
Abstract: This article defends two arguments proposed by Robert Grosseteste for the view that the Incarnation is logically prior to the Fall. Each of them is motivated by the goodness of Christ as a creature who is nonetheless worthy of worship, though the first considers this fact as an intrinsic good, and the second considers it as instrumentally good, by virtue of its making possible fleshly communion between God and his creatures. I will then consider Bonaventure's reasons for rejecting these arguments, which turn on the worry that they posit a divine obligation to become Incarnate. I show that while Bonaventure's concern is reasonable, he addresses it at the unacceptable cost of denying important aspects of the Incarnation's purpose in the actual world. However, Bonaventure accepts that the Incarnation and Passion are "necessary" for human redemption in a way that is consistent with divine freedom, an intuition which Aquinas brings to particularly clear expression by analyzing the Incarnation as necessary in the sense of being the most fitting means of salvation. Applying this line of thought to Christ's flesh, considered as the fitting instrument by which God has elected to perfectly beatify humanity, allows us to reconcile Grosseteste's insistence on the Incarnation's priority to the Fall with Bonaventure's insistence on its absolute gratuity.